Welfare of Employment and Unemployment Due to Covid-19 in Gianyar Regency - Itarini, Ni Made; Yuliarmi, Ni Nyoman; Marhaeni, A.A. I.N (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 2, Agustus 2022 (pp.162-339)DO - 10.24843/JEKT.2022.v15.i02.p08, 2022)
Workers always want sustainable prosperity. The Ministry of Manpower uses the Employment Development Index (EDI) to measure the success of labor development. The EDI indicator which has decreased from 2019-2020 is the welfare indicator caused by Covid-19 beginning of 2020. The purpose of this study is to analyze effect the level of health, creativity, and networking on productivity and welfare, and examine the levels of health, creativity, and networking with productivity that affect on the welfare of employment and unemployment due to Covid-19 in Gianyar Regency. This research uses primary data collected under the accidental sampling method combined with snowball sampling. The analysis technique used is Partial Least Square analysis. The results showed that the level of health, creativity, and networking had a positive and significant effect on productivity and welfare, and productivity mediates effect the level of health, creativity, and networking on welfare of employment and unemployment due to Covid-19 in Gianyar Regency.